2018
DOI: 10.1002/dneu.22635
|View full text |Cite
|
Sign up to set email alerts
|

High‐Salt Exposure During Perinatal Development Enhances Stress Sensitivity

Abstract: Excess consumption of dietary sodium during pregnancy has been shown to impair offspring cardiovascular function and enhance salt preference in adulthood, but little is known regarding the long-term impact of this nutritional surplus on offspring brain morphology and behavior. Using a combination of cellular and behavioral approaches, we examined the impact of maternal salt intake during the perinatal period on structural plasticity in the prefrontal cortex (PFC) and nucleus accumbens (NAc) in weanling and adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In turn, this can lead to the release of inflammatory signals, resulting in neuroinflammation, loss of function, and, consequently, in behavioral changes (Hatanaka et al, 2016;Cirulli et al, 2020;Dias et al, 2020;Maciel August et al, 2020). Previous studies in rodents have shown that HS diets caused an imbalance in the brain redox state, with decreased cognition (Liu et al, 2014;Ge et al, 2017;Faraco et al, 2019) and increased reactivity to stressful situations (Bai et al, 2017;Dingess et al, 2018). Moreover, a HS diet in the preconception, gestation, and lactation periods has been shown to negatively influence the redox state of the cerebellum, hypothalamus, and hippocampus of the offspring (Stocher et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, this can lead to the release of inflammatory signals, resulting in neuroinflammation, loss of function, and, consequently, in behavioral changes (Hatanaka et al, 2016;Cirulli et al, 2020;Dias et al, 2020;Maciel August et al, 2020). Previous studies in rodents have shown that HS diets caused an imbalance in the brain redox state, with decreased cognition (Liu et al, 2014;Ge et al, 2017;Faraco et al, 2019) and increased reactivity to stressful situations (Bai et al, 2017;Dingess et al, 2018). Moreover, a HS diet in the preconception, gestation, and lactation periods has been shown to negatively influence the redox state of the cerebellum, hypothalamus, and hippocampus of the offspring (Stocher et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents that used dietary or water salt supplementation (2–8%) confirm these findings, reporting impaired cognition, aggravation of cerebral ischemic injury, and high-stress responsivity ( Ge et al, 2017 ; Faraco et al, 2018 , 2019 ; Mitchell et al, 2018 ; Gilman et al, 2019a ; Zhang et al, 2020 ). Importantly, preclinical studies suggest that the maternal high-salt diet can also induce changes in locomotion, inhibition, and anxiety in the offspring, when fed in the preconception, gestation, or lactation periods ( Mcbride et al, 2008 ; Mecawi and Almeida, 2017 ; Dingess et al, 2018 ). During these periods, the offspring is highly susceptible to dietary salt, which may impact on development, potentially leading to lifelong changes in metabolism and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, preclinical studies using affective measures in rodents show mixed results, with maternal obesity found to increase [ 26 , 30 , 31 , 39 , 41 , 53 ] or decrease anxiety -like behaviour [ 27 , 38 , 43 , 49 ]. The age at which behaviour was measured may impact on these findings.…”
Section: Cognitive and Behavioural Effects Of Maternal Obesity/matermentioning
confidence: 99%
“…Experimental studies have suggested that early high salt exposure may increase stress sensitivity, involving changes to the structural plasticity of the prefrontal cortex (PFC) and nucleus accumbens (NAc) [ 13 ]. Both the PFC and NAc have been found to be involved in reward processing [ 37 ], and our previous work found that those areas also participated in high SP [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…High salt intake is an important risk factor associated with elevated BP and is related to psychological stress. Experimental studies have found that early high salt exposure may increase the risk of stress-related neuropsychiatric disorders and stress sensitivity [ 13 , 14 ]. In the USA, a significant increase in BP was observed during and after the COVID-19-related lockdown [ 15 ], which was explained by the authors as partially due to the emotional stress of the lockdown.…”
Section: Introductionmentioning
confidence: 99%